As pinturas murais deslocadas pela Direção Geral dos Edifícios e Monumentos Nacionais : proposta de roteiro - Camilo, Ana (2019)
The present essay is created on behalf of a master’s degree in Museology and Museography, whose main purpose is to study the mural paintings displaced by the Direção Geral dos Edifícios e Monumentos Nacionais (General Direction of National Buildings and Monuments), and their exhibition, by presenting a proposal for a final route for visits. In this context, there is a knowledge of nine Romanic churches that were intervened in the period between 1932 and 1970, located in Minho and Trás-os- Montes, whose paintings were detached by DGEMN. In most cases, this operation was only performed on some panels, continuing the remaining paintings in their original location. So, the priority was always given to panels containing figurative scenes, ignoring the decorative scenes of the composition. In this work, the investigation is divided in several chapters. It begins with a brief introduction to DGEMN - its history, surroundings and their performance, fundamental for the comprehension of the work done and the methodologies used, as well as the motivations that led to the option of intervening in specific monuments in detriment of others. Next, the detached mural paintings are presented – their location, their historical and artistic background, the interventions they were subjected to during their deployment and subsequently, as well as their state of conservation and current location. It is then addressed the issue of the role of mural painting in both situations: in its place of origin and in museums, as regards its function and its museology by trying to understand how these paintings, that were taken from the place of origin, can gain a new language and function without, however, losing their religious, catechizer, devotional and decorative character. At the end of this work, it will be presented a proposal for a visit to these paintings, which can be found in museums and in churches where they have been relocated in some cases